Reliability analysis of prestressed concrete bridges under prevailing truck traffic in Pakistan - Shams, Hamza; Qiu, Yanjun; Kashif, Muhammad; Ullah, Hanif; Abdrhman, Hamid; Fu, Jianfeng; Yang, Enhui (Građevinski materijali i konstrukcije, 2025)
This paper presents a comprehensive reliability assessment of prestressed concrete bridges in Pakistan subjected to prevailing truck traffic conditions. The study compares actual load effects from weigh-in-motion (WIM) data with design specifications from the Pakistan Highway Bridge (PHB) Code (1967) and AASHTO LRFD. Statistical analysis of axle weights, configurations, and gross vehicle weights (GVW) reveals that 72.7% of trucks exceed legal load limits, with 5-axle trucks showing 97% non-compliance. Reliability analysis using First-Order Second Moment (FOSM) methods indicates that existing bridge designs exhibit significant variations in safety margins, with reliability indices (b) ranging from 2.51 (Chitral Bridge) to 5.6 (Bannu Road Bridge). The results demonstrate that current design codes do not accurately represent Pakistan's truck traffic, leading to potential overstressing or underutilization of bridges. The study recommends revising live load models based on empirical traffic data and implementing stricter enforcement of weight regulations to enhance bridge safety and longevity.